Power at sea. - Rose, Lisle A., 1936- (University of Missouri Press, 2007)
"[Volume 1] Traces the social issues, technological advances, and combative encounters of the international naval race from 1890 through WWI, as the largest industrial nations (U.S, Great Britain, Japan, and Germany) scrambled to secure global markets and empire, using their battleship navies as pawns of power politics"--Provided by publisher